Analysis of Narrative Functionality: Toward Evidence-based Approaches in Managed Care Settings - Olness, Gloria Streit; Gyger, Jennifer; Thomas, Kathy (Seminars in Speech and Language, 2012)
The advent of managed health care has challenged rehabilitation professionals to guide their clients toward functionally meaningful outcomes in the least amount of time possible and to justify the evidence base for their intervention approaches. The ability to relate personal narratives in everyday contexts lies at the core of communicative functionality, but feasible clinical assessment of narrative has proven elusive. The purpose of this article is to offer an evidence-based framework for guiding assessments of the personal narratives of adults with aphasia, within a managed care model of service delivery. A literature-based model of narrative functionality is proposed, and a targeted set of criterion-referenced measures and behavioral observations derived from this model are suggested as potential metrics of narrative functionality. The authors do not intend to prescribe exact methods of narrative evaluation, but rather to suggest possible directions for professionals to develop evidence-based clinical narrative analysis tailored to the functional assessment needs of their clients across a variety of service settings.
Keywords: Narrative; assessment; aphasia; managed care